Ankle Brachial Index Values, Leg Symptoms, and Functional Performance Among Community‐Dwelling Older Men and Women in the Lifestyle Interventions and Independence for Elders Study. Issue 6 (12th November 2013) - McDermott, Mary M.; Applegate, William B.; Bonds, Denise E.; Buford, Thomas W.; Church, Timothy; Espeland, Mark A.; Gill, Thomas M.; Guralnik, Jack M.; Haskell, William; Lovato, Laura C.; Pahor, Marco; Pepine, Carl J.; et al.
Abstract : Background: The prevalence and significance of low normal and abnormal ankle brachial index (ABI) values in a community‐dwelling population of sedentary, older individuals is unknown. We describe the prevalence of categories of definite peripheral artery disease (PAD), borderline ABI, low normal ABI, and no PAD and their association with lower‐extremity functional performance in the LIFE Study population. Methods and Results: Participants age 70 to 89 in the LIFE Study underwent baseline measurement of the ABI, 400‐m walk, and 4‐m walking velocity. Participants were classified as follows: definite PAD (ABI <0.90), borderline PAD (ABI 0.90 to 0.99), low normal ABI (ABI 1.00 to 1.09), and no PAD (ABI 1.10 to 1.40). Of 1566 participants, 220 (14%) had definite PAD, 250 (16%) had borderline PAD, 509 (33%) had low normal ABI, and 587 (37%) had no PAD. Among those with definite PAD, 65% were asymptomatic. Adjusting for age, sex, race, body mass index, smoking, and comorbidities, lower ABI was associated with longer mean 400‐m walk time: (definite PAD=533 seconds; borderline PAD=514 seconds; low normal ABI=503 seconds; and no PAD=498 seconds [ P <0.001]). Among asymptomatic participants with and without PAD, lower ABI values were also associated with longer 400‐m walk time ( P <0.001) and slower walking velocity ( P =0.042). Conclusion: Among older community‐dwelling men and women, 14% had PAD and 49% had borderline or low normal ABI values. Lower ABI values were associated with greater functional impairment, suggesting that lower extremity atherosclerosis may be a common preventable cause of functional limitations in older people. Clinical Trial Registration: URL:http://clinicaltrials.gov/ Unique identifier: NCT01072500.